PENGARUH FAKTOR INTERNAL DAN EXTERNAL DIRI SUMBER DAYA MANUSIA TERHADAP MINAT BERWIRAUSAHA - Akhmad Suharto* Rudi Kusubagio** Abadi Sanosra*** M. Mishbah A**** (Universitas Muhammadiyah Jember, 2015)
This study aims to investigate the influence of internal factors and external human resources themselves against interest in entrepreneurship. The object of this study was student of economic faculty of University of Muhammadiyah Jember which has a sample of 90 students with a record that already take entrepreneurship courses. The sampling technique using Stratified Random Sampling.The technique of collecting data using interviews, questionnaires and data analysis tools using multiple linear regression. Based on the partial results of the study analyzes internal factors themselves, significant effect on student interest in entrepreneurship with a beta coefficient of 2.637 and sig. 0,010. While partially self external factors, significantly influence student interest in entrepreneurship with external factor beta coefficient of 5.630 and sig themselves. 0,000. simultaneous internal and external factors themselves human resources significantly affect the interest in entrepreneurship students with koefifien beta value of 121.394 and sig. 0,000, as well as the most dominant variable is the external factors affecting themselves with the coefficient 5.630. This is not consistent with the hypothesis that in the wake that the most dominant variable influencing factor is the internal self.